Penerapan E-Government dalam Pembangunan Demokrasi Pemerintahan Desa di Kabupaten Gowa, Indonesia - Anas, Andika; Arifin, Indar; Irwan, A Lukman; Ansar, Muhammad Chaeroel (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2024)
The use of e-government in Gowa Regency's villages to improve democracy is the subject of this study. The primary issue facing village governance in the digital age is how information technology may be used to increase citizen participation, transparency, and accountability. This study is unique in that it examines how e-government interacts with the still-unexplored village governance context. The main inquiries this study aims to address are: What ways may the Gowa Regency's village governments be made more democratic through the use of e-government ? In three villages in Gowa Regency, case studies were used in the research method, which was qualitative. Observation, interviews, documentation, and literature review were used to gather data. According to the findings, using e-government improved community engagement, boosted budget management transparency, and promoted village government accountability. The major finding is that e-government has a lot of promise to improve village governance through democracy. The necessity for digital literacy and a strong technological foundation, as well as the importance of village governments in promoting public engagement and ensuring openness and accountability in the use of information technology, are all important implications. This study adds significantly to the local and international literature on e-government and local democracy by providing a new understanding of how e-government is used to strengthen democracy in the context of village governance.